Cloning and preliminary functional analysis of OsGRF6 gene in regulating primary root development in rice - YU Qingqing; SHAN Yushuang; SHANG Huixin; ZENG Chuan; ZHANG Zeyong (Xibei zhiwu xuebao, 2024)
[Objective] OsGRF6 belongs to the GRF family and is involved in the regulation of plant growth and development as well as tolerance to abiotic stress. The purpose of this study was to explore the molecular mechanism of OsGRF6 in regulating the primary root development of rice, and provide clues for the in-depth understanding of OsGRF6 function in regulating root development in rice. [Methods] The transcription factor gene OsGRF6 was cloned from the rice variety ‘ZH11’ by PCR. The evolutionary tree construction and promoter analysis were carried out. The genotype analysis, qRT-PCR identification, and phenotype observation of OsGRF6-OE (overexpression line) and osgrf6 (mutant) were carried out. The binding sequence of OsGRF6 was detected through yeast one-hybrid assays, and the target genes downstream of OsGRF6 were analyzed through ChIP-seqs and RNA-seqs data. [Results] (1) OsGRF6 contained the conservative domains of QLQ and WRC, which is closely related to AtGRF1, AtGRF2, and OsGRF7. The promoter region of OsGRF6 contained multiple cis-acting elements responding to abiotic stress and hormones. (2) The expression of OsGRF6 was high in seeds, young spikes, and roots, but was low in leaves. Subcellular localization analysis showed that OsGRF6 was located in the nucleus, and OsGRF6 had transcription activation activity. (3) Compared with the wild type, overexpression of OsGRF6 showed a longer primary root, while loss of function mutant osgrf6 showed a shorter primary root. (4) OsGRF6 bond to the CGGCA sequence. (5) Using the ChIP-seq and RNA-seq assays, it was found that many Os- GRF6 target genes were involved in regulating rice root development, such as OsARF7 and OsARF4, etc. [Conclusion] In addition to regulating rice architecture and seed development, OsGRF6 also regulates rice root development by regulating the expression of genes involved in the auxin pathway, such as OsARF7 and OsARF4, etc.